ANALISIS PENGARUH SALES GROWTH, LIKUIDITAS, DAN ASSET TANGIBILITY TERHADAP STRUKTUR MODAL - Rifky Belva Effanda; Anna Marina; Gita Desipradani (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
The rapid growth of companies in the food and beverage sub-sector in Indonesia requires management to formulate appropriate financial strategies, one of which is through the management of capital structure. Capital structure reflects the combination of debt and equity used in company operations to maintain business continuity and increase competitiveness. This study aims to analyze the effect of sales growth, liquidity, and asset tangibility on capital structure in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period.The research method used is a quantitative approach with secondary data. Sampling was carried out using a purposive sampling technique with a total of 162 observations from 27 companies. Data processing was performed using SPSS version 26 software.The results showed that simultaneously, sales growth, liquidity, and asset tangibility had a significant effect on capital structure with a significance value of 0.000. Partially, all three variables had a significant negative effect on capital structure, with asset tangibility being the most dominant variable. The coefficient of determination (Adjusted R²) value of 0.933 indicates that 93.3% of the variation in capital structure can be explained by the three independent variables in this model. These findings emphasize the importance of considering these three factors in corporate financing strategies within the food and beverage sector.